CONTEXTUAL TEACHING AND LEARNING TECHNIQUE IN IMPROVING STUDENTS’ ABILITY TO WRITE DESCRIPTIVE SENTENCE - Hasanah, Maulidiyah; Salam, Urai; Novita, Dewi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstrak : Penggunaan tehnik pembelajaran kontekstual dalam pengajaran menulis teks deskriptif efektif untuk meningkatkan pemahaman siswa akan teks deskriptif. Hal ini dibuktikan dari hasil belajar siswa pada siklus pertama dan siklus kedua. Nilai mean pada siklus pertama adalah 52.7 yang dikategorikan dibawah standard ketuntasan. Sedangkan pada siklus kedua nilai mean yang dicapai adalah 77.1 yang dapat dikategorikan diatas standard ketuntasa. Nilai mean mengindikasikan bahwa kemampuan siswa dalam menulis teks deskriptif meningkat dengan menggunakan teknik pembelajaran kontekstual. Melalui penelitian ini penulis dapat menunjukkan bahwa kemampuan siswa menulis teks deskriptif dapat meningkat dengan menggunakan teknik pembelajaran kotekstual. Kata Kunci: mengajar, menulis, deskriptif, teknik pembelajaran kontekstual Abstract : Using contextual teaching and learning technique in teaching desriptive writing was effective to improve the achievement in writing a descriptive text. It was shown by the students’ score achievement from the first cycle to the second cycle. The mean score of the first cycle is 52.7. It is categorized below the students’ standard achievement. The mean score of the second test is 77.1. It is categorized above the students’ standard achievement. The mean score indicated the improvement on the students’ descriptive sentence writing achievement by teaching use contextual teaching and learning approach. At the second cycle there were more improvement on students’ descriptive sentence writing. The result was better than the first result. Through this research the writer shows that the students’ descriptive sentence writing achievement can be improved by using contextual teaching and learning technique. Key Words: teaching, writing, descriptive, contextual teaching and learning technique